Peritoneal dialysis in an end-stage renal disease patient with massive ascites and primary liver cancer - Lulu Sun; Chunmei Liang; Yuqin Wang; Hui Li; Lijun Yao; Huajun Jiang (Renal Failure)
End-stage renal disease (ESRD) coexisted with cirrhosis, ascites, and primary liver cancer represents an extraordinarily rare clinical condition that typically occurs in very late-stage decompensated cirrhosis and is associated with an extremely poor prognosis. We present a case of a 68-year-old male patient with ESRD who experienced various decompensated complications of liver cirrhosis, particularly massive ascites and hepatic space-occupying lesions. Peritoneal dialysis (PD) catheter insertion and continuous ambulatory peritoneal dialysis (CAPD) treatment were successfully performed. During meticulous follow-up, the patient survived for one year but ultimately succumbed to complications related to liver cancer. PD can serve as an efficacious therapeutic approach for such late-stage patients afflicted together with severe cirrhosis, massive ascites and primary liver cancer.